1998
DOI: 10.1126/science.282.5386.92
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Climate Changes in Antarctica and the North Atlantic

Abstract: Central Greenland ice cores provide evidence of abrupt changes in climate over the past 100,000 years. Many of these changes have also been identified in sedimentary and geochemical signatures in deep-sea sediment cores from the North Atlantic, confirming the link between millennial-scale climate variability and ocean thermohaline circulation. It is shown here that two of the most prominent North Atlantic events-the rapid warming that marks the end of the last glacial period and the Bolling/Allerod-Younger Dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
209
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 317 publications
(227 citation statements)
references
References 42 publications
14
209
0
4
Order By: Relevance
“…To answer such questions there is a need to obtain more isotopic records with the best possible resolution at various places in Antarctica. This need is strengthened by the data recently obtained from the Taylor Dome core (hereafter TD), which on the published timescale appears to indicate synchronous climatic changes between this Ross Sea sector of Antarctica and the North Atlantic [Steig et al, 1998]. [1998] used an old timescale for the Vostok core which caused them to incorrectly conclude that both Byrd and Vostok cooled earlier than TD.…”
mentioning
confidence: 97%
“…To answer such questions there is a need to obtain more isotopic records with the best possible resolution at various places in Antarctica. This need is strengthened by the data recently obtained from the Taylor Dome core (hereafter TD), which on the published timescale appears to indicate synchronous climatic changes between this Ross Sea sector of Antarctica and the North Atlantic [Steig et al, 1998]. [1998] used an old timescale for the Vostok core which caused them to incorrectly conclude that both Byrd and Vostok cooled earlier than TD.…”
mentioning
confidence: 97%
“…US scientists concentrated on sites easily accessible from McMurdo with two drillings completed respectively in 1994 and 1999, a 554 m drilled at Taylor Dome using the PICO drill Steig et al, 1998) and a 1004 m core retrieved at Siple Dome using the GISP-2 drill (Gow and Engelhardt, 2000;Taylor et al, 2004). Both cores gave access to ice from the last glacial period.…”
Section: Deep Drillings In Antarcticamentioning
confidence: 99%
“…However, regional difference in the warming rate from the last glacial to Holocene is significant [88]. It's interesting to point out that the stable isotopic record of the Taylor ice core from the Coast of Ross Sea [85] during the last deglaciation corresponds reversely to that of the ice cores mentioned above, but Stenni et al [88] indicated the dating lethality of the Taylor core [88].…”
Section: Temperature Change At Millennial To Sub-millennial Timescalesmentioning
confidence: 98%